New Testament Theology: Too Theological, Too Difficult, and Too Repetitive? - Michael F. Bird (Religions, 2022)
This essay argues that New Testament Theology (NTT) is an indispensable mediating discipline between historical exegesis and systematic theology. It defends NTT against claims that: (1) NTT should be replaced by the study of early Christian religion; (2) The NT is too diverse and disparate to sustain any unifying theology; and (3) NTT has been over-done so that there is nothing new to be said. The essay proceeds to the defense of NTT by contending that theology is part of the substance and significance of the NT. In addition, the NT contains several varieties and unities that can simultaneously challenge and aid theological reflection. Finally, the essay proposes a fresh approach to explicate the theological texture and religious impetus of the NT with a view to renewing living faith communities.